Self-Efficacy, Work Environment, and Compensation on Motivation and its Affects Employee Performance - Darmawan, Devin Fadillah (PRODUKTIF: Jurnal Kepegawaian dan Organisasi, 2023)
Human resources are also very important things to pay attention to. If the human resources are good, it will also be good for the continuity of these business activities or vice versa. Basically, in a business world, it is said that the performance of a company is very dependent on the performance of its employees. The purpose of this study is to determine the effect of self-efficacy, work environment and compensation on motivation that has an impact on the performance of PT Alia Jaya Anugerah Bekasi employees. This research is descriptive quantitative, statistical calculations used in the form of simple linear regression and continued with multiple linear regression. The samples taken were employees of PT Alia Jaya Anugerah Bekasi as many as 92 respondents and used a saturated sampling method. The analytical techniques in this study are descriptive, validity test, reliability test, classical assumption test, linear regression test, coefficient of determination test and finally is a hypothesis test. The results of data analysis show that the multiple linear regression equation is Y = 1.952 + 0.649 (X1) + 0.120 (X2) + 0.148 (X3) with an Adjusted R Square determination coefficient of 0.460 or 46% where the meaning is that self-efficacy (X1), work environment (X2) and compensation (X3) have a contribution effect of 46%. Meanwhile, the remaining 54% is influenced by other factors.